Peróxido de hidrogênio: importância e determinação - Mattos, Ivanildo Luiz de [UNESP]; Shiraishi, Karina Antonelli [UNESP]; Braz, Alexandre Delphini [UNESP]; Fernandes, João Roberto [UNESP] (Sociedade Brasileira de Química, 2003)
A brief discussion about the hydrogen peroxide importance and its determination is presented. It was emphasized some consideration of the H2O2 as reagent (separated or combined), uses and methods of analysis (techniques, detection limits, linear response intervals, sensor specifications). Moreover, it was presented several applications, such as in environmental, pharmaceutical, medicine and food samples.
Hydrogen peroxide: importance and determination
Keywords: hydrogen peroxide; sensors; biosensors